FAKTOR RENDAHNYA KESADARAN MASYARAKAT DALAM MEMBAYAR ZAKAT DI INDONESIA - Ilham Alivian; Kevin Shaquille Lesmana; Mohamad Faizul Amri Budianto; Siobhan Rusdi Abdulaziz Jatmala (Universitas Muhammadiyah Prof Dr Hamka, 2023)
Zakat is one of the five pillars of Islam that every Muslim carries, which can be interpreted as something that increases or grows. Indonesia itself, Zakat has not become a serious instrument in its implementation, both from its collection, and management, to distribution. In this study, we will discuss the definition of Zakat, the pillars, and conditions of Zakat, Zakat management, Zakat institutions, and the contribution of Zakat toreducing poverty. This study aims to determine the extent of awareness of the Indonesian people in paying Zakat. The research technique uses qualitative methods, in data collection techniques using library research methods, where sources and references or information materials come from journals, internet media, theses, and others. The technique used to analyze the data is a descriptive method, where each variable will be explained one by one. Based on the results of the study, several factors that cause the low payment of Zakat, such as the need for digitalization of Zakat, community resources in Zakat are still not qualified, the lack of transparency of Zakat management institutions, the absence of mandatory Zakat government policies and the development of Zakat infrastructure which is lacking.